Education in black and white : Myles Horton and the Highlander Center's vision for social justice - Preskill, Stephen, 1950- (University of California Press, 2021)
"How Myles Horton and the Highlander Folk School catalyzed social justice and democratic education. For too long, the story of life-changing teacher and activist Myles Horton has escaped the public spotlight. An inspiring and humble leader whose work influenced the Civil Rights Movement, Horton helped thousands of marginalized people gain greater control over their lives. Born and raised in early twentieth-century Tennessee, Horton was appalled by the disrespect and discrimination that was heaped on poor people-both black and white-throughout Appalachia. He resolved to create a place, available to all, where regular people could talk to each other, learn from one another, and get to the heart of issues of class and race and right and wrong. And so in 1932, Horton cofounded the Highlander Folk School, smack in the middle of Tennessee. Education in Black and White is the first biography of Myles Horton in 25 years and focuses, in particular, on the educational theories and strategies he first developed at Highlander to serve the interests of the poor, the marginalized, and the oppressed. His personal vision became an essential influence on everyone from Rosa Parks and Martin Luther King, Jr., to Eleanor Roosevelt and Congressman John Lewis. Stephen Preskill chronicles how Myles Horton gained influence as an advocate for organized labor, an activist for civil rights, a supporter of Appalachian self-empowerment, an architect of an international popular education network, and a champion for direct democracy, showing how the example he set remains education's last best hope today"--